2009
DOI: 10.1109/tpami.2008.79
|View full text |Cite
|
Sign up to set email alerts
|

Robust Face Recognition via Sparse Representation

Abstract: We consider the problem of automatically recognizing human faces from frontal views with varying expression and illumination, as well as occlusion and disguise. We cast the recognition problem as one of classifying among multiple linear regression models and argue that new theory from sparse signal representation offers the key to addressing this problem. Based on a sparse representation computed by l{1}-minimization, we propose a general classification algorithm for (image-based) object recognition. This new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
6,427
5
29

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8,724 publications
(6,647 citation statements)
references
References 39 publications
39
6,427
5
29
Order By: Relevance
“…The feature extraction is targeted to certain invariances and tailored to the sparse classifier. We have shown that sparse classification as introduced by Wright et al (2009) is well suited for human event detection. Sparse classification offers a set of advantages over other methods for the problem of action recognition and event detection, being robust, adaptive and easy to tune.…”
Section: Discussion Conclusion and Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…The feature extraction is targeted to certain invariances and tailored to the sparse classifier. We have shown that sparse classification as introduced by Wright et al (2009) is well suited for human event detection. Sparse classification offers a set of advantages over other methods for the problem of action recognition and event detection, being robust, adaptive and easy to tune.…”
Section: Discussion Conclusion and Summarymentioning
confidence: 99%
“…This representation is sparse because it should contain only vectors from the class to which the test vector belongs (Wright et al, 2009). …”
Section: Sparse Classification and Event Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, sparse representation classifier (SRC) [3] and collaborative representation classifier (CRC) [4] have gained much attention for hyperspectral imagery classification. Different from the traditional classifiers, such as support vector machine (SVM), these representation-based classifiers do not use the training-testing fashion.…”
Section: Introductionmentioning
confidence: 99%